Ten-Year Anniversary of the International Journal of Neonatal Screening: Revisiting Its Scope - Ralph Fingerhut; Peter C. J. I. Schielen (International Journal of Neonatal Screening, 2025)
The 10th anniversary of the International Journal of Neonatal Screening (IJNS) was celebrated on 25 March 2025, during the 13th Regional European Meeting of the International Society of Neonatal Screening (ISNS) in Luxembourg [...]